Supervisi Akademik Kunjungan Kelas oleh Kepala Sekolah dalam Rangka Meningkatkan Kinerja Guru - Samsul Hadi (FONDATIA, 2019)
This study aims to determine how the implementation of academic supervision of class visits by school principals in order to improve the performance of teachers in SMP NW Jerua and can provide technical assistance and guidance to teachers to be able to improve the quality of performance in carrying out tasks and carrying out teaching and learning processes. This research is a qualitative study using descriptive methods. To describe this research, a measurement will be carried out on the implementation planning and evaluation of the academic supervision of class visits by the school principal in NW Jerua Middle School. For this reason, this research is intended to find out more about the data collection about the academic planning documents for class visits, the academic supervision documents for class visits, the academic supervision documents for class visits. The informants in this study were the principal and teachers at NW Jerua Middle School. Data collection techniques in this study using observation techniques, documentation studies, and interviews. Observations were made to obtain data and conditions of academic supervision by the principal's class visit to improve teacher performance in NW Jerua Middle School by direct observation. Documentation studies are conducted to view and obtain authentic data that can be used to match the same data using other techniques. Interview with the teacher as an informant to get information related to the academic supervision techniques of class visits. The flow of this research reveals academic supervision in the NW Jerua Middle School. The supervision management system is as follows: The headmaster conducts academic supervision supervision of the visit by discussing with the teacher first. Then conduct academic supervision of class visits by applying principles and preparing instruments. The final stage is the evaluation and academic follow-up of class visits.